The Influence Of Tax Understanding, Taxpayer Awareness And Tax Sanctions On The Compliance Of E-Commerce Actors In Fulfilling Tax Obligations (Case Study of Individual Taxpayers of E-commerce Actors in DKI Jakarta Province, Indonesia) - Helwa Syazwana Azkya; Nisa, Farhatun (International Journal of Management and Business Economics, 2024)
The main problem of taxation in Indonesia is the low level of taxpayer compliance, which is caused by minimal awareness and understanding of tax obligations and neglect of tax aspects of online transactions by e-commerce actors. This study aims to analyze the effect of tax understanding, taxpayer awareness, and tax sanctions on the compliance of e-commerce actors in DKI Jakarta Province. The research method used is a quantitative approach with a sample of 100 e-commerce actors selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using a t-test (partial). The results of the study indicate that tax understanding, taxpayer awareness, and tax sanctions have a positive and significant effect on e-commerce actor compliance. Based on these findings, it is recommended that the government increase tax socialization and education programs and apply strict sanctions to improve taxpayer compliance in the e-commerce sector.